if 3times 3rd term is equal to the 7times 7th term then find 10th term
Answers
Answered by
2
3(a3) = 7(a7)
⇒ 3(a+2d) = 7(a+6d)
⇒ 3a + 6d = 7a+42d
⇒ 7a-3a +42d -6d = 0
⇒ 4a + 36d = 0
⇒ a+9d = 0
⇒ a = -9d --------------------------------------`1
a10 = a+9d
⇒ -9d +9d [From 1]
⇒ a10 = 0
∴ a10 = 0
Thank You......!!!!!!!!!
Mark as brainliest if helpful...
Yours, Jahnavi.
⇒ 3(a+2d) = 7(a+6d)
⇒ 3a + 6d = 7a+42d
⇒ 7a-3a +42d -6d = 0
⇒ 4a + 36d = 0
⇒ a+9d = 0
⇒ a = -9d --------------------------------------`1
a10 = a+9d
⇒ -9d +9d [From 1]
⇒ a10 = 0
∴ a10 = 0
Thank You......!!!!!!!!!
Mark as brainliest if helpful...
Yours, Jahnavi.
Similar questions